The Analysis of Word Formation Process in Song Album â€œTraumazineâ€ by Megan Thee Stallion - Anjelia, Delsi Fadilah; Ramdhani, Muhammad Iqbal (Universitas Nahdlatul Ulama Blitar, 2024)
Songs can be used to express ideas or emotions, or even as a way for people to communicate with one another. One area of linguistics, morphology, deals with how language structure might be used to analyze meanings or feelings in song lyrics. In this study, the word formation process for the song Megan Thee Stallion from the album â€œTraumazineâ€ will be analyze. Descriptive research is the qualitative method employed in this study. The word formation hypothesis of George Yule (2019) is used by the researcher. The 18 songs on Megan Thee Stallionâ€™s album â€œTraumazineâ€ provided the source of the data used in this research. The â€œtraumazineâ€ album by Megan Thee Stallion contains 8 of the 14 different kinds of word formation process that were examined in this study. This study discovered 34 data on word formation process. There are three data from borrowing, seven from ccompounding, three from blending, ten from clipping, one each from hypocorisms and backformation, eight from acronyms, and one from multiple processes. Based on the findings, Megan Thee Stallionâ€™s song albu â€˜Traumazineâ€ most dominantly uses the clipping process to create words